Students’ procedural knowledge on simplex method in linear programming: An explanatory sequential design - Rellon, Louie Resti Sandoval; Corsonado, Jeramie Castillo (Indonesian Journal of Science and Mathematics Education, 2024)
This study employed a sequential explanatory mixed-methods design to assess students' procedural knowledge in linear programming using the simplex method through quantitative tests, qualitative interviews, and Focus Group Discussions (FGD). The objective was to uncover students' understanding of the step-by-step procedure in the simplex method, with results indicating a low level of knowledge (38.31%) in solving linear programming problems. Thematic analysis from the qualitative phase identified students' perceptions of the problem-solving process. Based on these findings, it is recommended that educators adopt more in-depth and multifaceted teaching strategies to enhance students' procedural understanding. This research has implications for developing teaching strategies to improve students' procedural knowledge in linear programming.